Sexual Activity After Dysvascular Lower Extremity Amputation - Henderson, Alison W. (Rehabil Psychol, 2016)
OBJECTIVE: This study examined the prevalence and correlates of sexual activity among individuals experiencing their first dysvascular lower extremity amputation. DESIGN: A prospective cohort was recruited from 4 Veterans Affairs Medical Centers. Of 198 potential participants who met inclusion criteria, 113 (57%) agreed to participate within 7 days of amputation (baseline) and 6 weeks, 4 months, and 12 months post-amputation; 105 completed the sexual activity items at baseline. Measures included self-reported frequency of sexual activity; desire for more or less sexual activity; importance of sexual activity to satisfaction with life; Patient Health Questionnaire—9; Locomotor Capability Index—5; pain intensity/frequency; quality of life. RESULTS: Depending on the time period post-amputation, 11%–24% reported engaging in any sexual activity, although a majority indicated that sexual activity is very important to their satisfaction with life. Frequency of sexual activity increased between 6 weeks and 4 and 12 months post-amputation. In univariate analyses, older age was associated with decreased sexual activity at all time points; at 4 and 12 months, greater mobility was associated with increased sexual activity. In multivariable models, mobility was associated with sexual activity at 4 and 12 months; age and race remained associated with sexual activity at 4 and 12 months, respectively. At all time points, frequency and importance of sexual activity were significantly associated with one another. CONCLUSIONS: Although a minority of individuals engaged in any sexual activity during the study period, it remained an important factor in overall satisfaction with life. Younger age and improved mobility were associated with increased sexual activity. Rehabilitation specialists are encouraged to address sexuality and, if relevant, incorporate it into rehabilitation goals.